Determination of Training, Occupational Safety and Health (K3) on Job Satisfaction - Setyo Widodo, Djoko (International Journal of Advanced Multidisciplinary, 2023)
This researchdiscusses Determination of Career Development, Training and Occupational Safety and Health (K3) to Job Satisfaction. The purpose of this study is to find out whether career development, training and occupational safety and health (K3) affect job satisfaction. The research method used is descriptive qualitative, which aims to obtain hypotheses for further research. The results of this study include: 1) Career Development affects Job Satisfaction; 2) Training affects Job Satisfaction; and 3) Occupational Safety and Health affects Job Satisfaction.